Age-related differences in metacognition for memory capacity and selectivity. Issue 9 (21st October 2019) - Siegel, Alexander L. M.; Castel, Alan D.
ABSTRACT: Background: We compared two types of metacognitive monitoring in younger and older adults: metacognitive accuracy for their overall memory performance and their ability to selectively remember high-value information. Method: Participants studied words paired with point values and were asked to maximise their point score. In Experiment 1, they predicted how many words they would remember while in Experiment 2, they predicted how many points they would earn. Results: In Experiment 1, while younger adults were accurate in their predictions, older adults were overconfident in the number of words they would recall throughout the task. In Experiment 2, however, both younger and older adults were equally accurate when predicting the amount of points they would earn after some task experience. Conclusions: While younger adults may have higher metacognitive accuracy for their capacity, older adults can accurately assess their ability to selectively remember information, suggesting potentially separate metacognitive mechanisms that are differentially affected by aging.